Nursing professionals' views on the workplace - B.J. Erasmus (AOSIS, 1998)
This article reports on a survey done among registered, enrolled and auxiliary nurses registered with the South African Nursing Council. The survey was carried out in the period from the end of December 1997 to the beginning of 1998. The purpose of the survey was to obtain the views of female nurses on various aspects of the workplace. The important findings were the fact that nurses liked working as part of a team and that this contributed the most to th eir job satisfaction. The item that contributed least to job satisfaction was pay. The most important problems were that they felt that they were not paid enough and that they need better benefits. The majority of nurses were however positive about their jobs and the items the highest on the list of career expectations were job satisfaction, followed by a need for recognition.